Pemanfaatan Larva BSF (Black Soldier Fly) Sebagai Metode Pengomposan Limbah Sisa Makanan Dan Dedaunan - Savira Laily Hendriatiningsih; Shaila Insyirah Medina; Ina Hafidah Affan; Sekar Ramadhita Syach Al-Fitriani; Denny Oktavina Radianto (KOLONI, 2023)
Every activity carried out will produce waste, this results in high generation in Indonesia. The amount of waste generated needs to be processed in order to reduce the number of pollutions to the environment. Waste treatment basically uses the 3R principle, namely reduce, reuse, and recycle. One way of processing organic waste is by recycling it into compost. The composting process can occur naturally in the open, but the composting process will decompose more quickly if microorganisms are added to it. In this study, the composting process used black fly larvae or commonly called black soldier fly (BSF) larvae to simplify and speed up the process of decomposing organic waste into compost. The purpose of this study is to determine the quality of organic waste fertilizer produced from composting using BSF larvae. Composting organic waste using BSF was carried out for 15 days in a reactor box. A total of 5000 grams of composted organic waste produces 550 grams of compost with a reduced percentage of 11%. The resulting compost has a characteristic blackish brown color, smell and texture resembling soil, temperature 29°C, pH 5.5, water content contained in the compost is 11% and C content in the compost is 55.21%. From the results of the study, it can be concluded that the characteristics of compost produced from composting using BSF larvae for pH and C content parameters do not meet the quality standards for compost from organic waste in SNI 19-7030-2004 concerning Specifications for compost from domestic organic waste. Keywords: BSF, organic waste, compost.